Advances in determining the gross tumor target volume for radiotherapy of brain metastases - Du, Shanshan; Gong, Guanzhong; Liu, Rui; Meng, Kangning; Yin, Yong (Frontiers in Oncology, 2024)
Brain metastases (BMs) are the most prevalent intracranial malignant tumors in adults, and are the leading cause of mortality attributed to malignant brain diseases. Radiotherapy (RT) plays a critical role in the treatment of BMs, with local RT techniques such as stereotactic radiosurgery (SRS)/stereotactic body radiotherapy (SBRT) showing remarkable therapeutic effectiveness. The precise determination of gross tumor target volume (GTV) is crucial for ensuring the effectiveness of SRS/SBRT. Multimodal imaging techniques such as CT, MRI, and PET are extensively used for the diagnosis of BMs and GTV determination. With the development of functional imaging and artificial intelligence (AI) technology, there are more innovative ways to determine GTV for BMs, which significantly improve the accuracy and efficiency of the determination. This article provides an overview of the progress in GTV determination for RT in BMs. Keywords： Brain metastases, Gross tumor target volume, Radiation therapy, MRI, Artificial